Evaluación docente para la mejora continua en el cantón Latacunga - Vichisela Tulmo, Nelly Yolanda (2017)
The teacher evaluation has a very important element in the educational quality. Nowadays educational exercise demands teachers with a high level of professional development in order to face new challenges in the society. The present research is about teacher evaluation for continuous improvement contributed as a process that allowed to evaluate and value the teachers, and contribute the continuous development of its actions, acquiring as a basis the analysis of its needs and possibilities, which admitted to implant the important anomalies that occurred in the professional occupation, to balance their strengths and weaknesses, in order to emphasize the difficulties and strengthen the benefits achieved in order to understand that teacher evaluation is part of the educational process to reach educational excellence. For the effective development of this research technique it applied the survey with a sample of 334 teachers at different educational institutions from Latacunga Canton, which helped to ratify the problem under research. Therefore, it used the inductive-deductive method, which deal with problem from the overall review to specify the origin of the teacher evaluation for continuous improvement in function of quality and efficiency. Also it used the formative research, taking into account that through this research it will spread the information that benefits and strengthen to teachers in order to develop new knowledge and skills in their profession; the bibliographical research with which the problem is based on existing bibliographic information, books, magazines and publications; the field investigation because it allowed to research, the problem in the place of the facts to obtain detailed information according to the objectives. In this research, it proposed conclusions and recommendations of the results obtained through the applied survey with its respective analysis and interpretation, which will allow to improve the education system.